Proteome study of Francisella tularensis live vaccine strain-containing phagosome in Bcg/Nramp1 congenic macrophages: resistant allele contributes to permissive environment and susceptibility to infection - Kovárová, Hana; Halada, Petr; Man, Petr; Golovliov, Igor; Krocová, Zuzana; Spacek, Josef; Porkertová, Stanislava; Necasová, Radka (Proteomics, 2002)
The phagocytosis of pathogens by macrophages classically initiates maturation of the phagosome that involves a dynamic exchange of phagosomal components with intracellular compartments of the endocytic pathway. The intracellular microorganisms have developed sophisticated mechanisms to sense environmental conditions and respond to them by phenotypic alterations that ensure their adaptation, survival and proliferation inside the cell. They have learned also to utilise host cellular components to ensure own survival. Recent results suggest that the Bcg locus/Nramp1 gene (natural resistance-associated macrophage protein 1) controls natural resistance to infection by Francisella tularensis LVS (live vaccine strain) and its effect is opposite to that observed for other Bcg/Nramp1-controlled pathogens such as several mycobacterial species, Leischmania donovani, and Salmonella typhimurium. In the case of F. tularensis LVS infection, the mutant allele of the Bcg locus (Bcg(s)/Nramp1(s)) is associated with natural resistance and, inversely, the wild type allele (Bcg(r)/Nramp1(r)) confers susceptibility. To determine whether differential allelic expression of the Bcg locus/Nramp1 gene modifies the composition of F. tularensis LVS-containing phagosomes (FCP), we have utilised an approach where we isolated FCP from infected Bcg congenic B10R (Bcg(r)/Nramp1(r)) and B10S (Bcg(s)/Nramp1(s)) macrophages of susceptible and resistant phenotype, respectively. Comparative proteomic analysis of the two phagosomal compartments with subsequent mass spectrometric analysis allowed identification of several proteins typical for FCP from B10R macrophages. They include a bacterial hypothetical 23 kDa protein, 60 kDa chaperonin GroEL, and host putative proteins that appeared to be mitochondrial ATP synthase beta-chain and NADH-ubiquinone oxidoreductase based on high cross-species homology. High abundance of the hypothetical 23 kDa protein correlates with the susceptible phenotype and, possibly, pathogenicity of F. tularensis LVS. The results demonstrate that F. tularensis LVS can exploit ion transport function of Bcg/Nramp1 to its own advantage.
Keywords: alely; proteom; 2D gelová elektroforéza; proteiny přenášející kationty; Microscopy, Electron; Cation Transport Proteins; Francisella tularensis; Bacterial Vaccines; Phagosomes; Phenotype; Alleles; Disease Susceptibility; náchylnost k nemoci; bakteriální vakcíny; fagozomy; Flow Cytometry; fenotyp; Electrophoresis, Gel, Two-Dimensional; Proteome; průtoková cytometrie; elektronová mikroskopie